2013
DOI: 10.1007/s00284-013-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Household Bacterial Community and Analysis of Species Shared with Human Microbiome

Abstract: Microbial populations in indoor environments, where we live and eat, are important for public health. Various bacterial species reside in the kitchen, and refrigerators, the major means of food storage within kitchens, can be a direct source of food borne illness. Therefore, the monitoring of microbiota in the refrigerator is important for food safety. We investigated and compared bacterial communities that reside in the vegetable compartment of the refrigerator and on the seat of the toilet, which is recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 31 publications
1
68
1
1
Order By: Relevance
“…The genus Enhydrobacter has been found in widely diverse environments like athletic equipment (Wood et al 2015), skin (buttocks) (Zeeuwen et al 2012), toilet samples (Jeon et al 2013), and a beer bottling plant (Timke et al 2005). A search in BLAST (http://blast.ncbi.nlm.nih.gov/ Blast.cgi) revealed a 100% match to both Moraxella osloensis and Enhydrobacter aerosaccus for the OTU and isolates representing genus Enhydrobacter in our study.…”
Section: Proteobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Enhydrobacter has been found in widely diverse environments like athletic equipment (Wood et al 2015), skin (buttocks) (Zeeuwen et al 2012), toilet samples (Jeon et al 2013), and a beer bottling plant (Timke et al 2005). A search in BLAST (http://blast.ncbi.nlm.nih.gov/ Blast.cgi) revealed a 100% match to both Moraxella osloensis and Enhydrobacter aerosaccus for the OTU and isolates representing genus Enhydrobacter in our study.…”
Section: Proteobacteriamentioning
confidence: 99%
“…Near-fulllength 16S rRNA gene sequences of 1 random isolate (classified as genus Enhydrobacter) confirmed that our isolates were most similar to these 2 species (99% identity, data not shown). Both Moraxella osloensis and Enhydrobacter aerosaccus have been found in skin microbiota (Gao et al 2007;Jeon et al 2013). Moraxella osloensis has also been found in the biofilm of various pipe materials in drinking water distribution systems (Zhu et al 2014) and is the bacterium responsible for the locker-room smell or shower-curtain odor (Kubota et al 2012).…”
Section: Proteobacteriamentioning
confidence: 99%
“…Sequences of gajami-sikhae from pyrosequencing system were analyzed according to previous description. 26) Sequences were sorted by a unique barcode in each sample, and removed by read length (<300 bp) and average quality score (<25). Primer sequences were trimmed by pairwise alignment, and sequencing errors were corrected.…”
Section: Methodsmentioning
confidence: 99%
“…Raw sequence data was processed by previously reported literature [24]. According to the demultiplexing step, low quality reads (read length <300 bp) were removed for further quality analysis.…”
Section: Biodiversity Analysis and Antibiotic Resistance Gene Databasementioning
confidence: 99%